Analyzing and Evaluating E-Participation Levels on the Websites of Indonesian Government Ministries: A Case Study of BKPerdag - Alvisha Najwannida; Nurdin (Journal of Governance and Social Policy, 2026)
This study analyzes public e-participation in the implementation of e-government by the Indonesian Ministry of Trade through the Badan Kebijakan Perdagangan (BKPerdag) website to improve public services. This research applies a descriptive qualitative approach by collecting data through interviews, website observation, and public service documentation. The analysis uses Le Blanc's (2020) e-participation framework, which consists of e-information, e-consultation, and e-decision-making. The findings show that the BKPerdag website has functioned effectively as an entry point for public information and services, particularly through analytical publications, research/interview services, internship services, audience requests, PPID, WhatsApp, HERO, SP4N-LAPOR!, and satisfaction surveys. Public participation is strongest at the e-information and e-consultation levels because users can access information, download documents, ask questions, and provide feedback. However, participation at the e-decision-making level remains limited because there is no clear mechanism showing how public input influences policy decisions. Therefore, the BKPerdag website contributes positively to public service improvement, but it still needs stronger channel integration, better usability, and a more transparent feedback mechanism.Keywords: E-participation, E-government, BKPerdag, Public Service, Government Website